Glass fiber composite material
By using metallocene catalytic polypropylene and Ziegler-Natta catalytic heterophasic propylene copolymers with wide molecular weight distribution, combining glass fibers to form high-performance fiber-reinforced composites, the problems of high emissions and insufficient performance in the prior art are solved. , achieving low emissions, high performance and high productivity effects.
Patent Information
- Application Number
- CN202380039847.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-31
- Publication Date
- 2024-12-20
AI Technical Summary
Existing glass fiber reinforced polypropylene composites produce high emissions during the manufacturing process and are difficult to meet the requirements of high productivity and low emissions. At the same time, their properties such as heat deformation resistance and impact resistance are insufficient.
Using metallocene catalytic polypropylene and Ziegler-Natta-catalyzed heterophase propylene copolymers with wide molecular weight distribution, combining glass fibers and compatibilizers to form a specific fiber-reinforced composite material to ensure polypropylene and heterophase The proportion and structure of propylene copolymer and glass fibers improve the performance of the material.
It achieves low emissions, improves the heat deformation and impact resistance of the material, and improves productivity, meeting the requirements of high performance and environmental protection.
Smart Images

Figure BDA0005128794630000071 
Figure BDA0005128794630000112 
Figure BDA0005128794630000121
Abstract
Description
Technical Field
[0001] The present invention relates to a fiber reinforced composite material comprising polypropylene, a heterophasic propylene copolymer and glass fiber and a product comprising the fiber reinforced composite material. Background Art
[0002] Polypropylene is a material widely used in various technical fields, and reinforced polypropylene is particularly significant in fields that previously relied entirely on non-polymer materials (especially metals). A specific example of reinforced polypropylene is a glass fiber reinforced polypropylene composite. By selecting the type of polypropylene, the amount of glass fiber, and sometimes by selecting the type of compatibilizer used, such materials can adjust the performance of the composite. Therefore, today, glass fiber reinforced polypropylene composites are recognized materials for applications that require high stiffness, heat deformation resistance and impact resistance. However, a disadvantage of commercially available fiber reinforced polypropylene composites is their fairly high emissions, which is due to the relatively large amount of oligomers obtained as by-products in the polymerization process and the free radical induced degradation (commonly referred to as visbreaking) that may be required to increase melt flow rate (MFR2) and processability. This is related to the fact that not only the final performance of the fiber reinforced polypropylene composite needs to be considered, but also the products made therefrom need to be manufactured in an effective manner, i.e., the fluidity of the composite must be quite high.
[0003] Therefore, there is a need for a glass fiber reinforced polypropylene composite material which is rigid and has a substantially high resistance to heat deformation and low emissions and which can be further processed with high production rates. Summary of the invention
[0004] The present invention has found that fiber reinforced polypropylene composites must include metallocene-catalyzed polypropylene and Ziegler-Natta-catalyzed heterophasic propylene copolymers having broad molecular weight distribution. Therefore, it is preferred that both polymers have not been visbroken, i.e. modified in a free radical induced process to reduce the molecular weight.
[0005] Therefore, the present invention relates to a fiber-reinforced composite material comprising
[0006] (a) based on a fiber-reinforced composite material, 30 to 60 wt. % of a polypropylene (PP1),
[0007] (b) 10 to 40 wt.-%, based on the fiber reinforced composite, of a heterophasic propylene copolymer (HECO), wherein the heterophasic propylene copolymer (HECO) comprises a propylene homopolymer (H-PP2) and an ethylene-propylene rubber (EPR),
[0008] (c) based on the fiber-reinforced composite material, 10 to 40 wt.% of glass fiber (GF), and
[0009] (d) 0.05 to 5.0 wt. % of a compatibilizer (CA), based on the fiber-reinforced composite material,
[0010] The total amount of the polypropylene (PP1), the heterophasic propylene copolymer (HECO), the glass fibers (GF) and the compatibilizer (CA) in the fiber reinforced composite material is at least 95 wt.%,
[0011] wherein further, the polypropylene (PP1) has
[0012] (i) a melt flow rate MFR2 (230° C., 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min,
[0013] (ii) not more than 0.5% by weight 13 Comonomer content, if present, determined by C-NMR spectroscopy, where ethylene is the comonomer,
[0014] (iii) a molecular weight distribution (MWD) as determined by gel permeation chromatography (GPC) in the range of greater than 4.5 to less than 8.5, and
[0015] (iv) Pass in the range of 0.20 to 1.00% 13 2,1 regio defects determined by C-NMR spectroscopy,
[0016] Wherein still further, the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) has
[0017] (v) Pass in the range of 0 to less than 0.10% 13 2,1 regiodefects determined by C-NMR spectroscopy.
[0018] Further preferred embodiments of the composite material are defined in the claims dependent on claim 1 and are also defined in more detail below.
[0019] The invention also relates to an article, preferably an automotive article, comprising at least 95% by weight of the fiber-reinforced composite material according to the invention. DETAILED DESCRIPTION
[0020] In the following a fiber reinforced composite material will be defined in more detail and subsequently the components of said composite material will be defined.
[0021] Fiber-reinforced composites
[0022] The present invention relates to a fiber reinforced composite material, which comprises polypropylene (PP1), a heterophasic propylene copolymer (HECO), glass fibers (GF) and a compatibilizer (CA). The fiber reinforced composite material is understood to be known in the art. That is, the polypropylene (PP1) together with the heterophasic propylene copolymer (HECO) forms the dominant part of the continuous phase in which the glass fibers are embedded. When the glass fibers are short glass fibers, the fibers are dispersed in a polymer mixture comprising polypropylene (PP1) and the heterophasic propylene copolymer (HECO), wherein the polymer mixture acts as a continuous phase. The compatibilizer (CA) improves the adhesion between the polar glass fibers and the non-polar polymer mixture, and the non-polar polymer mixture comprises polypropylene (PP1) and the heterophasic propylene copolymer (HECO).
[0023] Therefore, the present invention relates to a fiber-reinforced composite material comprising
[0024] (a) 30 to 60 wt.-%, preferably 35 to 55 wt.-%, of a polypropylene (PP1), based on the fiber-reinforced composite material,
[0025] (b) 10 to 40 wt.-%, preferably 20 to 35 wt.-%, based on the fiber reinforced composite, of a heterophasic propylene copolymer (HECO), wherein the heterophasic propylene copolymer (HECO) comprises a propylene homopolymer (H-PP2) and an ethylene-propylene rubber (EPR),
[0026] (c) 10 to 40 wt. %, preferably 15 to 30 wt. %, of glass fiber (GF), based on the fiber-reinforced composite material, and
[0027] (d) 0.05 to 5.0 wt. %, preferably 0.1 to 5.0 wt. %, of a compatibilizer (CA), based on the fiber-reinforced composite material,
[0028] The total amount of the polypropylene (PP1), the heterophasic propylene copolymer (HECO), the glass fibers (GF) and the compatibilizer (CA) in the fiber reinforced composite material is at least 95 wt%, preferably at least 97 wt%.
[0029] Besides these four components typical additives may be present, for example added to increase the lifetime of the polypropylene (PP1) and the heterophasic propylene copolymer (HECO), ie antioxidants (see definition of additives below).
[0030] Therefore, the present invention relates to a fiber-reinforced composite material comprising
[0031] (a) based on a fiber-reinforced composite material, 35 to 55 wt. % of a polypropylene (PP1),
[0032] (b) 20 to 35 wt.-%, based on the fiber reinforced composite, of a heterophasic propylene copolymer (HECO), wherein the heterophasic propylene copolymer (HECO) comprises a propylene homopolymer (H-PP2) and an ethylene-propylene rubber (EPR),
[0033] (c) based on fiber-reinforced composite materials, 15 to 30 wt. % of glass fibers (GF),
[0034] (d) 0.1 to 5.0 wt. % of a compatibilizer (CA), based on the fiber-reinforced composite material, and
[0035] (e) 0.1 to 5.0 wt. % of an additive (AD), based on the fiber-reinforced composite material,
[0036] wherein the total amount of polypropylene (PP1), heterophasic propylene copolymer (HECO), glass fiber (GF), compatibilizer (CA) and additive (AD) in the fiber reinforced composite material is at least 98 wt.-%, preferably in the range of 98 to 100 wt.-%, such as in the range of 99 to 100 wt.-%.
[0037] In a specific embodiment, the fiber-reinforced composite material according to the present invention is preferably composed of the following:
[0038] (a) based on a fiber-reinforced composite material, 35 to 55 wt. % of a polypropylene (PP1),
[0039] (b) 20 to 35 wt.-%, based on the fiber reinforced composite, of a heterophasic propylene copolymer (HECO), wherein the heterophasic propylene copolymer (HECO) comprises a propylene homopolymer (H-PP2) and an ethylene-propylene rubber (EPR),
[0040] (c) based on fiber-reinforced composite materials, 15 to 30 wt. % of glass fibers (GF),
[0041] (d) 0.1 to 5.0 wt. % of a compatibilizer (CA), based on the fiber-reinforced composite material, and
[0042] (e) 0.1 to 5.0 wt. % of additives (AD), based on the fiber-reinforced composite material.
[0043] As mentioned above the continuous phase of the fiber reinforced composition is mainly dominated by the polypropylene (PP1) and the heterophasic propylene copolymer (HECO). Accordingly it is preferred that the continuous phase of the fiber reinforced composition wherein the glass fibers are embedded comprises at least 97 wt.-%, more preferably at least 98 wt.-% of a mixture consisting of the polypropylene (PP1) and the heterophasic propylene copolymer (HECO).
[0044] Further, due to the presence of the heterophasic propylene copolymer (HECO), the fiber reinforced composition contains an elastomeric polymer, i.e., ethylene-propylene rubber (EPR). An elastomeric polymer is understood to be a polymer that does not form a continuous phase in a (semi) crystalline polypropylene. In other words, the elastomeric polymer is dispersed in the (semi) crystalline polypropylene, i.e., an inclusion is formed in the (semi) crystalline polypropylene. A polymer containing an elastomeric polymer as an inclusion as a second polymer phase is referred to as heterophasic. For example, the presence of a second polymer phase or so-called inclusion can be seen by high-resolution microscopy (such as electron microscopy or atomic force microscopy) or by dynamic mechanical thermal analysis (DMTA). Specifically, in DMTA, the presence of a heterophasic structure can be identified by the presence of at least two different glass transition temperatures. Therefore, the polymer phases of the fiber reinforced composition according to the present invention themselves form a system in which the polypropylene (PP1) forms a continuous phase together with the propylene homopolymer (H-PP2) in which the ethylene-propylene rubber (EPR) is dispersed.
[0045] Accordingly, it is preferred that the weight ratio of the mixture of the polypropylene (PP1) and the propylene homopolymer (H-PP2) acting as the matrix to the ethylene-propylene rubber (EPR) dispersed in the matrix [((PP1) + (H-PP2) / (EPR)] is in the range of 75:25 to 95:5, more preferably in the range of 80:20 to 92:8.
[0046] Furthermore it is preferred that the weight ratio between the polypropylene (PP1) and the propylene homopolymer (H-PP2) [(PP1) / (H-PP2)] is in the range of 60:40 to 80:20, more preferably in the range of 68:32 to 77:23.
[0047] Additionally, it is preferred that the molecular weights of the polypropylene (PP1) and the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) are rather similar. Accordingly, it is preferred that the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) has a melt flow rate MFR2 (230°C, 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, more preferably in the range of 50.0 to 150 g / 10 min, provided that the melt flow ratio MFR2 between the polypropylene (PP1) and the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) [MFR2(PP1) / MFR2(H-PP2)] is in the range of 0.75 to 1.25, more preferably in the range of 0.80 to 1.20.
[0048] Further, it is preferred that the fiber reinforced composite material has a melt flow rate MFR2 (230° C., 2.16 kg) measured according to ISO 1133 in the range of 8.0 to 50 g / 10 min, more preferably in the range of 10 to 30 g / 10 min.
[0049] The fiber-reinforced composite material according to the invention is particularly characterized by low emissions. Therefore, it is preferred that the fiber-reinforced composite material has a VOC (volatile organic compound) value determined according to VDA 278 (October 2011) of less than 150 μg / g, more preferably in the range of 50 to less than 150 μg / g, still more preferably in the range of 60 to 100 μg / g.
[0050] It is further preferred that the fiber reinforced composite material has a tensile modulus measured on injection molded samples according to ISO 527-1 at 1 mm / min in the range of 3500 to 7000 MPa, more preferably in the range of 3800 to 6500 MPa, such as in the range of 4000 to 63000 MPa. In addition, the fiber reinforced composite material preferably has an elongation at break in the same tensile test of greater than 2.0%, more preferably in the range of 2.1 to 10.0%, such as in the range of 2.2 to 8.0%.
[0051] In addition to or in lieu of the requirements of the preceding paragraph, the fiber-reinforced composite material has a thermal conductivity of 30.0 to 75.0 kJ / m 2 In the range of 35.0 to 70.0 kJ / m 2 In the range of 40.0 to 65.0 kJ / m 2 Charpy impact strength measured at 23°C according to ISO 179-1eU in the range.
[0052] In a very specific embodiment the fiber reinforced composite material has a heat deformation temperature HDT measured according to ISO 75B under a load of 0.46 MPa in the range of 146 to 160°C, more preferably in the range of 148 to 158°C, such as in the range of 150 to 156°C.
[0053] Polypropylene (PP1)
[0054] An essential component of the present invention is the polypropylene (PP1), which needs to be carefully selected to achieve the desired properties. Therefore, the polypropylene (PP1) according to the present invention must be produced using a metallocene catalyst and such produced polypropylene must have a rather broad molecular weight distribution (MWD).
[0055] Accordingly, the polypropylene (PP1) is produced in the presence of a specific metallocene catalyst, as defined in more detail below. The polypropylene produced in the presence of a metallocene catalyst is characterized by the misinsertion of monomer units during the polymerization process compared to the polypropylene produced in the presence of a Ziegler-Natta catalyst. Thus, the polypropylene (PP1) according to this invention has a certain amount of 2,1-regio defects, which indicates that it was produced using a metallocene catalyst. I.e. the polypropylene (PP1) according to this invention has an amount of 2,1-regio defects in the range of 0.20 to 1.00 %, more preferably in the range of 0.40 to 0.90 %. 13 2,1 regiodefects determined by C-NMR spectroscopy.
[0056] Thus, the polypropylene (PP1) according to this invention has
[0057] (i) a melt flow rate MFR2 (230° C., 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, preferably in the range of 50.0 to 150 g / 10 min,
[0058] (ii) not more than 0.5% by weight 13 The comonomer content was determined by C-NMR spectroscopy. The comonomer was ethylene.
[0059] (iii) a molecular weight distribution (MWD) as determined by gel permeation chromatography (GPC) in the range of greater than 4.5 to less than 8.5, preferably in the range of 5.5 to 8.0, and
[0060] (iv) in the range of 0.20 to 1.00%, more preferably in the range of 0.40 to 0.90% 13 2,1 regiodefects determined by C-NMR spectroscopy.
[0061] More preferably, the polypropylene (PP1) according to this invention has
[0062] (i) a melt flow rate MFR2 (230° C., 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, preferably in the range of 50.0 to 150 g / 10 min,
[0063] (ii) not more than 0.5% by weight 13 The comonomer content was determined by C-NMR spectroscopy. The comonomer was ethylene.
[0064] (iii) a molecular weight distribution (MWD) determined by gel permeation chromatography (GPC) in the range of greater than 4.5 to less than 8.5, preferably in the range of 5.5 to 8.0,
[0065] (iv) in the range of 0.20 to 1.00%, more preferably in the range of 0.40 to 0.90% 13 2,1 regio defects determined by C-NMR spectroscopy, and
[0066] (v) Melting temperature Tm determined by DSC according to ISO 11357-3 (heating and cooling rate 10°C / min) in the range of 150 to 159°C.
[0067] It is especially preferred that the polypropylene (PP1) is a propylene homopolymer (H-PP1).
[0068] Accordingly, it is preferred that the polypropylene (PP1) of the instant invention is a propylene homopolymer (H-PP1) having the following properties:
[0069] (i) a melt flow rate MFR2 (230° C., 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, preferably in the range of 50.0 to 150 g / 10 min,
[0070] (ii) a molecular weight distribution (MWD) as determined by gel permeation chromatography (GPC) in the range of greater than 4.5 to less than 8.5, preferably in the range of 5.5 to 8.0, and
[0071] (iii) in the range of 0.20 to 1.00%, more preferably in the range of 0.40 to 0.90% 13 2,1 regiodefects determined by C-NMR spectroscopy.
[0072] Further, the polypropylene (PP1), preferably the propylene homopolymer (H-PP1), has a considerable amount of polymer, which elutes by Temperature Rising Elution fractionation (TREF) below 100° C. Accordingly, it is preferred that the polypropylene (PP1) has a fraction eluting by Temperature Rising Elution fractionation (TREF) below 100° C. in the range of 12 to 20 wt.-%, more preferably in the range of 14 to 18 wt.-%.
[0073] Therefore, it is preferred that the polypropylene (PP1) has
[0074] (i) a melt flow rate MFR2 (230° C., 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, preferably in the range of 50.0 to 150 g / 10 min,
[0075] (ii) not more than 0.5% by weight13 The comonomer content was determined by C-NMR spectroscopy. The comonomer was ethylene.
[0076] (iii) a molecular weight distribution (MWD) determined by gel permeation chromatography (GPC) in the range of greater than 4.5 to less than 8.5, preferably in the range of 5.5 to 8.0,
[0077] (iv) in the range of 0.20 to 1.00%, more preferably in the range of 0.40 to 0.90% 13 2,1 regio defects determined by C-NMR spectroscopy, and
[0078] (v) In the range of 12 to 20 wt%, more preferably in the range of 14 to 18 wt% of the fraction eluted at less than 100°C by temperature rising elution fractionation (TREF).
[0079] Still yet more preferably, the polypropylene (PP1) is a propylene homopolymer (H-PP1) having
[0080] (i) a melt flow rate MFR2 (230° C., 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, preferably in the range of 50.0 to 150 g / 10 min,
[0081] (ii) a molecular weight distribution (MWD) determined by gel permeation chromatography (GPC) in the range of greater than 4.5 to less than 8.5, preferably in the range of 5.5 to 8.0,
[0082] (iii) in the range of 0.20 to 1.00%, more preferably in the range of 0.40 to 0.90% 13 2,1 regio defects determined by C-NMR spectroscopy, and
[0083] (iv) in the range of 12 to 20 wt%, more preferably in the range of 14 to 18 wt% of the fraction eluted at less than 100°C by temperature rising elution fractionation (TREF).
[0084] Furthermore, the polypropylene (PP1) can be further defined by its melting temperature and xylene solubles content.
[0085] Accordingly it is preferred that the polypropylene (PP1), especially the propylene homopolymer (H-PP1), has a melting temperature Tm determined by DSC according to ISO 11357-3 (heating and cooling rate 10°C / min) in the range of 150 to 159°C.
[0086] The polypropylene (PP1) according to this invention is further preferably featured by a very low xylene cold soluble (XCS) content, which is not achievable with Ziegler-Natta catalysts. Thus, in a preferred embodiment the polypropylene (PP1), more preferably the propylene homopolymer (H-PP1) according to this invention has a xylene cold soluble (XCS) fraction measured according to ISO 16152 (25°C) in the range of 0.5 to 3.0 wt.-%, more preferably in the range of 0.8 to 2.5 wt.-%.
[0087] As mentioned above it is preferred that the polypropylene (PP1) of the instant invention is produced by means of a specific metallocene catalyst. Thus, in a preferred embodiment the polypropylene (PP1), more preferably the propylene homopolymer (H-PP1), is produced by polymerizing propylene and optionally ethylene in the presence of a metallocene catalyst having formula (I):
[0088]
[0089] Each R 1 are independently the same or different and are hydrogen or a linear or branched C1-C6 alkyl group, wherein at least one R of each phenyl group 1 Not hydrogen,
[0090] R' is C1-C 10 A hydrocarbon group, preferably a C1-C4 hydrocarbon group, more preferably a methyl group, and
[0091] X is independently a hydrogen atom, a halogen atom, a C1-C6 alkoxy group, a C1-C6 alkyl group, a phenyl group or a benzyl group.
[0092] In the following the term "formula (I)" represents a metallocene catalyst as defined in the preceding paragraph.
[0093] Therefore, it is especially preferred that the polypropylene (PP1) has
[0094] (i) a melt flow rate MFR2 (230° C., 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, preferably in the range of 50.0 to 150 g / 10 min,
[0095] (ii) not more than 0.5% by weight 13 The comonomer content was determined by C-NMR spectroscopy. The comonomer was ethylene.
[0096] (iii) a molecular weight distribution (MWD) determined by gel permeation chromatography (GPC) in the range of greater than 4.5 to less than 8.5, preferably in the range of 5.5 to 8.0,
[0097] (iv) in the range of 0.20 to 1.00%, more preferably in the range of 0.40 to 0.90% 13 2,1 regio defects determined by C-NMR spectroscopy, and
[0098] (v) optionally, in the range of 12 to 20 wt. %, more preferably in the range of 14 to 18 wt. % of the fraction eluted by temperature rising elution fractionation (TREF) at less than 100° C.,
[0099] Therein the polypropylene (PP1) is produced by polymerizing propylene and optionally ethylene in the presence of a metallocene catalyst having formula (I) as defined above.
[0100] Still more preferably, the polypropylene (PP1) is a propylene homopolymer (H-PP1) having
[0101] (i) a melt flow rate MFR2 (230° C., 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, preferably in the range of 50.0 to 150 g / 10 min,
[0102] (ii) a molecular weight distribution (MWD) determined by gel permeation chromatography (GPC) in the range of greater than 4.5 to less than 8.5, preferably in the range of 5.5 to 8.0,
[0103] (iii) in the range of 0.20 to 1.00%, more preferably in the range of 0.40 to 0.90% 13 2,1 regio defects determined by C-NMR spectroscopy, and
[0104] (iv) optionally, in the range of 12 to 20 wt. %, more preferably in the range of 14 to 18 wt. % of the fraction eluted by temperature rising elution fractionation (TREF) at less than 100° C.,
[0105] Wherein the propylene homopolymer (H-PP1) is produced by polymerizing propylene in the presence of a metallocene catalyst having formula (I) as defined above.
[0106] Additionally, it is preferred that the polypropylene (PP1), such as the propylene homopolymer (H-PP1), is not visbroken. Visbreaking or controlled degradation by a free radical induced process initiated by peroxides or other free radical generators (radical generator) is generally used to increase the melt flow rate, thereby reducing the molecular weight and narrowing the molecular weight distribution. However, the degradation of the polymer, i.e. visbreaking, is obtained by using peroxides. Visbreaking and the use of peroxides may increase emission values (in terms of VOC or FOG) because undesirable side reactions may lead to an increase in the amount of oligomers. Further, the presence of peroxides may lead to undesirable discoloration of the polypropylene. In other words, it can be identified whether the polypropylene has been visbroken by the decomposition products of peroxides or other free radical generators and by the discoloration of the polypropylene. Therefore, whenever the term "non-visbroken" or "non-visbroken" is used hereinafter, it is understood that the melt flow rate, the molecular weight and the molecular weight distribution of the polypropylene (PP1) have not been altered by chemical or physical treatments and further, the polypropylene (PP1) does not contain decomposition products of peroxides or other free radical generators. In any case, further visbreaking is contrary to the teaching of the present invention, since it is desired that the polypropylene (PP1) of the present invention has a rather broad molecular weight distribution, which is inconsistent with visbreaking.
[0107] Therefore, it is preferred that the polypropylene (PP1) is not visbroken and has
[0108] (i) a melt flow rate MFR2 (230° C., 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, preferably in the range of 50.0 to 150 g / 10 min,
[0109] (ii) not more than 0.5% by weight 13 The comonomer content was determined by C-NMR spectroscopy. The comonomer was ethylene.
[0110] (iii) a molecular weight distribution (MWD) determined by gel permeation chromatography (GPC) in the range of greater than 4.5 to less than 8.5, preferably in the range of 5.5 to 8.0,
[0111] (iv) in the range of 0.20 to 1.00%, more preferably in the range of 0.40 to 0.90% 13 2,1 regio defects determined by C-NMR spectroscopy, and
[0112] (v) optionally, in the range of 12 to 20 wt. %, more preferably in the range of 14 to 18 wt. % of the fraction eluted by temperature rising elution fractionation (TREF) at less than 100° C.,
[0113] Therein the polypropylene (PP1) is produced by polymerizing propylene and optionally ethylene in the presence of a metallocene catalyst having formula (I) as defined above.
[0114] More preferably, the polypropylene (PP1) is a propylene homopolymer (H-PP1), wherein the propylene homopolymer (H-PP1) is not visbroken and has
[0115] (i) a melt flow rate MFR2 (230° C., 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, preferably in the range of 50.0 to 150 g / 10 min,
[0116] (ii) a molecular weight distribution (MWD) determined by gel permeation chromatography (GPC) in the range of greater than 4.5 to less than 8.5, preferably in the range of 5.5 to 8.0,
[0117] (iii) in the range of 0.20 to 1.00%, more preferably in the range of 0.40 to 0.90% 13 2,1 regio defects determined by C-NMR spectroscopy, and
[0118] (iv) optionally, in the range of 12 to 20 wt. %, more preferably in the range of 14 to 18 wt. % of the fraction eluted by temperature rising elution fractionation (TREF) at less than 100° C.,
[0119] Therein the propylene homopolymer (H-PP1) is produced by polymerizing propylene in the presence of a metallocene catalyst having formula (I) as defined above.
[0120] The polymerization of polypropylene is described in detail hereinafter.
[0121] The polypropylene (PP1) according to the present invention can be produced in one reactor or in a reactor cascade of two or more reactors, preferably two reactors. Since the polypropylene (PP1) according to the present invention must have a broad molecular weight distribution (MWD), i.e. at least 4.5, it is preferred to produce the polypropylene (PP1) in at least two reactors, producing polypropylene fractions with greatly different molecular weights in each reactor, thereby achieving a final polypropylene (PP1) with a broader molecular weight distribution (MWD), just as if the polypropylene (PP1) was produced in only one reactor. Polymerization processes suitable for producing the polypropylene (PP1) according to the present invention are known in the art. They comprise at least one polymerization stage, wherein the polymerization is typically carried out in solution, slurry, bulk or gas phase. Typically, the polymerization process comprises additional polymerization stages or reactors. In a particular embodiment, the process contains at least one bulk reactor zone and optionally at least one gas phase reactor zone, each zone comprising at least one reactor and all reactors are arranged in cascade. In a particularly preferred embodiment, the polymerization process comprises at least one bulk reactor and at least one gas phase reactor arranged in sequence. The process may also comprise a pre-reactor and a post-reactor. The pre-reactor typically comprises a pre-polymerization reactor. In such processes, the use of higher polymerization temperatures is preferred in order to achieve specific properties of the polymer. Typical temperatures in these processes are 70°C or higher, preferably 75°C or higher. As mentioned above, higher polymerization temperatures may be applied to some or all reactors in the reactor cascade.
[0122] Multimodal polymers can be produced according to several processes described in for example WO 92 / 12182, EP 0 887379 and WO 98 / 58976. The contents of these documents are incorporated herein by reference.
[0123] Preferably, the process for the production of the polypropylene (PP1) comprises two polymerization stages, wherein in the first polymerization stage a slurry reactor (SR), like a loop reactor (LR), is used and in the second polymerization stage a gas phase reactor is used.
[0124] The conditions in the first polymerization stage may be as follows:
[0125] - a temperature in the range of 70°C to 110°C, preferably between 72°C and 100°C, more preferably in the range of 75 to 90°C,
[0126] - a pressure in the range of 20 to 80 bar, preferably between 40 and 70 bar,
[0127] - adding hydrogen in a manner known per se to control the molar mass,
[0128] - In the case where a small amount of ethylene is contained in the polypropylene (PP1), ethylene is supplied.
[0129] Subsequently, the reaction mixture from the 1st polymerization stage is transferred to a gas phase reactor (GPR), where the conditions are preferably as follows:
[0130] - a temperature in the range of 50°C to 130°C, preferably between 60°C and 100°C,
[0131] - a pressure in the range of 5 to 50 bar, preferably between 15 and 40 bar,
[0132] - adding hydrogen in a manner known per se to control the molar mass;
[0133] - In the case where a small amount of ethylene is contained in the polypropylene (PP1), ethylene is supplied.
[0134] The residence time in the two reactor zones can vary.
[0135] In one embodiment of the process for producing polypropylene (PP1), the residence time in the slurry reactor (SR), such as the loop (LR), is in the range of 0.2 to 2.5 hours, such as 0.3 to 1.5 hours and the residence time in the gas phase reactor (GPR) is typically 0.8 to 6.0 hours, such as 1.0 to 4.0 hours.
[0136] The preferred multi-stage process is a "loop-gas phase" process such as that developed by Borealis (known as The slurry-gas phase process is described in the patent literature, for example in EP 0 887 379, WO 92 / 12182, WO 2004 / 000899, WO 2004 / 111095, WO 99 / 24478, WO 99 / 24479 or WO 00 / 68315. Another suitable slurry-gas phase process is the slurry-gas phase process of Basell. Craftsmanship.
[0137] As mentioned above the polypropylene (PP1) according to this invention is especially obtained in a polymerization process using a metallocene catalyst having formula (I)
[0138]
[0139] Each R 1 are independently the same or different and are hydrogen or a linear or branched C1-C6 alkyl group, wherein at least one R of each phenyl group 1 Not hydrogen,
[0140] R' is C1-C 10A hydrocarbon group, preferably a C1-C4 hydrocarbon group, more preferably a methyl group, and
[0141] X is independently a hydrogen atom, a halogen atom, a C1-C6 alkoxy group, a C1-C6 alkyl group, a phenyl group or a benzyl group.
[0142] Most preferably, X is chlorine, benzyl or methyl. Preferably, the two X groups are the same. The most preferred options are two chlorides, two methyls or two benzyls, especially two chlorides.
[0143] Particularly preferred metallocene catalysts of the present invention include:
[0144] Racemic-trans-dimethylsilylene[2-methyl-4,8-bis-(4'-tert-butylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylindene-1-yl]zirconium dichloride,
[0145] Racemic-trans-dimethylsilylene[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylindene-1-yl]zirconium dichloride,
[0146] Racemic-trans-dimethylsilylene[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(3',5'-di-tert-butylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride,
[0147] or its corresponding dimethyl zirconium analogue.
[0148] The most preferred catalyst is rac-trans-dimethylsilylene[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacen-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride.
[0149]
[0150] The ligands required to form the complex of the present invention and thus the catalyst can be synthesized by any process, and a skilled organic chemist can design various synthesis schemes to make the necessary ligand materials. For example, WO2007 / 116034 discloses the necessary chemical reactions. Synthesis schemes can also be found in WO 2002 / 02576, WO 2011 / 135004, WO 2012 / 084961, WO 2012 / 001052, WO 2011 / 076780, WO 2015 / 158790 and WO 2018 / 122134. With particular reference to WO 2019 / 179959, the most preferred catalysts of the present invention are described. The examples section also provides sufficient guidance for the technician.
[0151] Catalyst
[0152] In order to form an active catalytic species, it is generally necessary to employ a promoter which is well known in the art.
[0153] According to the present invention, a cocatalyst system comprising a boron-containing cocatalyst and / or an aluminoxane cocatalyst is used in combination with the metallocene catalyst complex defined above.
[0154] The aluminoxane cocatalyst may be one of formula (III):
[0155]
[0156] wherein n is generally 6 to 20, and R has the following meanings.
[0157] Aluminoxanes are formed after partial hydrolysis of organoaluminum compounds, such as compounds of the formula AlR3, AlR2Y and Al2R3Y3, wherein R can be, for example, C1-C 10 Alkyl, preferably C1-C5 alkyl, or C3-C 10 Cycloalkyl, C7-C 12 Aralkyl or alkaryl and / or phenyl or naphthyl, wherein Y can be hydrogen, halogen, preferably chlorine or bromine, or C1-C 10 Alkoxy groups, preferably methoxy or ethoxy groups. The oxygen-containing aluminoxanes obtained are usually not pure compounds but mixtures of oligomers of formula (III).
[0158] The preferred aluminoxane is methylaluminoxane (MAO).Since the aluminoxanes used as cocatalysts according to the invention are not pure compounds due to their mode of preparation, the molar concentrations of the aluminoxane solutions hereinafter are based on their aluminum content.
[0159] According to the present invention, it is also possible to use a boron-containing cocatalyst instead of the aluminoxane cocatalyst, or to use the aluminoxane cocatalyst in combination with the boron-containing cocatalyst.
[0160] The skilled person will recognize that when a boron-based cocatalyst is employed, the complex is typically pre-alkylated by reaction with an alkylaluminum compound such as TIBA. This procedure is well known and any suitable alkylaluminum may be used, for example Al(C1-C6 alkyl)3. Preferred alkylaluminum compounds are triethylaluminum, triisobutylaluminum, triisohexylaluminum, tri-n-octylaluminum and triisooctylaluminum.
[0161] Alternatively, when a borate cocatalyst is used, the metallocene catalyst complex is in its alkylated form, ie, for example, a dimethyl or dibenzyl metallocene catalyst complex may be used.
[0162] Boron-based cocatalysts of interest include those of formula (IV),
[0163] BY3(IV)
[0164] Wherein Y is the same or different and is a hydrogen atom; an alkyl group having 1 to about 20 carbon atoms; an aryl group having 6 to about 15 carbon atoms; an alkaryl group, an aralkyl group, a halogenated alkyl group or a halogenated aryl group, each group having 1 to 10 carbon atoms in the alkyl group and 6 to 20 carbon atoms in the aryl group; or fluorine, chlorine, bromine or iodine. Preferred examples of Y are methyl, propyl, isopropyl, isobutyl or trifluoromethyl, unsaturated groups such as aryl or halogenated aryl groups (e.g., phenyl, tolyl, benzyl, p-fluorophenyl, 3,5-difluorophenyl, pentachlorophenyl, pentafluorophenyl, 3,4,5-trifluorophenyl and 3,5-bis(trifluoromethyl)phenyl)). Preferred options are trifluoroborane, triphenylborane, tri(4-fluorophenyl)borane, tri(3,5-difluorophenyl)borane, tri(4-fluoromethylphenyl)borane, tri(2,4,6-trifluorophenyl)borane, tri(pentafluorophenyl)borane, tri(tolyl)borane, tri(3,5-dimethyl-phenyl)borane, tri(3,5-difluorophenyl)borane and / or tri(3,4,5-trifluorophenyl)borane.
[0165] Tris(pentafluorophenyl)borane is particularly preferred.
[0166] However, preference is given to using borates, i.e. compounds containing 3+ borate ions. Such ionic promoters preferably contain non-coordinating anions, such as tetrakis(pentafluorophenyl)borate and tetraphenylborate. Suitable counterions are protonated amines or aniline derivatives, such as methylammonium, aniline, dimethylammonium, diethylammonium, N-methylaniline, diphenylammonium, N,N-dimethylaniline, trimethylammonium, triethylammonium, tri-n-butylammonium, methyldiphenylammonium, pyridinium, p-bromo-N,N-dimethylaniline or p-nitro-N,N-dimethylaniline.
[0167] Preferred ionic compounds that can be used according to the present invention include: triethylammonium tetra(phenyl)borate, tributylammonium tetra(phenyl)borate, trimethylammonium tetra(tolyl)borate, tributylammonium tetra(tolyl)borate, tributylammonium tetra(pentafluorophenyl)borate, tripropylammonium tetra(dimethylphenyl)borate, tributylammonium tetra(trifluoromethylphenyl)borate, tributylammonium tetra(4-fluorophenyl)borate, N,N-dimethylcyclohexylammonium tetra(pentafluorophenyl)borate, N,N-dimethylbenzylammonium tetra(pentafluorophenyl)borate, N,N-dimethylanilinium tetra(phenyl)borate, N,N-diethylanilinium tetra(pentafluorophenyl)borate, N,N-dimethylanilinium tetra(pentafluorophenyl)borate, The present invention relates to N,N-di(propyl)ammonium tetrakis(pentafluorophenyl)borate, di(cyclohexyl)ammonium tetrakis(pentafluorophenyl)borate, triphenylphosphonium tetrakis(phenyl)borate, triethylphosphonium tetrakis(phenyl)borate, diphenylphosphonium tetrakis(phenyl)borate, tri(methylphenyl)phosphonium tetrakis(phenyl)borate, tri(dimethylphenyl)phosphonium tetrakis(phenyl)borate, triphenylcarbeniumtetrakis(pentafluorophenyl)borate or ferroceniumtetrakis(pentafluorophenyl)borate.
[0168] Preferred are triphenylcarbonium tetrakis(pentafluorophenyl)borate, N,N-dimethylcyclohexylammonium tetrakis(pentafluorophenyl)borate, or N,N-dimethylbenzylammonium tetrakis(pentafluorophenyl)borate.
[0169] Surprisingly, it has been found that certain boron promoters are particularly preferred. Therefore, preferred borates for use in the present invention include trityl ions. Therefore, the use of N,N-dimethylammonium tetrakis(pentafluorophenyl)borate and Ph3CB(PhF5)4 and the like is therefore particularly advantageous.
[0170] According to the present invention, preferred cocatalysts are aluminoxanes, more preferably methylaluminoxane, combinations of aluminoxanes with Al alkyls, boron or borate cocatalysts, and combinations of aluminoxanes with boron-based cocatalysts.
[0171] Suitable amounts of promoters are well known to the skilled person.
[0172] The molar ratio of boron to the metal ion of the metallocene may be in the range of 0.5:1 to 10:1 mol / mol, preferably in the range of 1:1 to 10:1 mol / mol, especially in the range of 1:1 to 5:1 mol / mol.
[0173] The molar ratio of Al in the aluminoxane to the metal ion in the metallocene may be in the range of 1:1 to 2000:1 mol / mol, preferably in the range of 10:1 to 1000:1 mol / mol, and more preferably in the range of 50:1 to 500:1 mol / mol.
[0174] The catalyst can be used in supported or unsupported form, preferably in supported form. The particulate support material used is preferably an organic or inorganic material, such as silicon dioxide, aluminum oxide or zirconium oxide or a mixed oxide, such as silicon dioxide-alumina, in particular silicon dioxide, aluminum oxide or silicon dioxide-alumina. The use of a silicon dioxide support is preferred. The skilled person is aware of the procedures required for supporting the metallocene catalyst.
[0175] Particularly preferably, the support is a porous material so that the complex can be loaded into the pores of the support, for example using processes similar to those described in WO94 / 14856 (Mobil), WO95 / 12622 (Borealis) and WO2006 / 097497.
[0176] The average particle size of the silica support is typically between 10 and 100 μm. However, it has proven to be particularly advantageous if the support has an average particle size of between 15 and 80 μm, preferably between 18 and 50 μm.
[0177] The average pore size of the silica support may be in the range of 10 to 100 nm, with a pore volume of 1 to 3 mL / g.
[0178] Examples of suitable support materials are, for example, ES757 manufactured and sold by PQ Corporation, Sylopol 948 manufactured and sold by Grace, or SUNSPERA DM-L-303 silica manufactured by AGC Si-Tech Co. The support may optionally be calcined before use in catalyst preparation to achieve an optimal silanol group content.
[0179] The use of such supports is conventional in the art.
[0180] Heterophasic polypropylene composition (HECO)
[0181] The second mandatory component of the fiber reinforced composition according to this invention is the heterophasic propylene copolymer (HECO).
[0182] The heterophasic propylene copolymer (HECO) according to the present invention comprises a matrix as a propylene homopolymer (HPP-2) and an ethylene-propylene rubber (EPR) dispersed therein. Therefore, the matrix contains (fine) dispersed inclusions that are not part of the matrix, and the inclusions contain ethylene-propylene rubber (EPR). As mentioned above, when defining the continuous phase of a fiber-reinforced composite material, the term "inclusions" indicates that the matrix and the inclusions form different phases in the heterophasic propylene copolymer (HECO). For example, the presence of a second phase or so-called inclusions can be seen by high-resolution microscopy (such as electron microscopy or atomic force microscopy) or by dynamic mechanical thermal analysis (DMTA). Specifically, in DMTA, the presence of a heterophasic structure can be identified by the presence of at least two different glass transition temperatures.
[0183] Thus, the heterophasic propylene copolymer (HECO) according to this invention comprises
[0184] (a) a propylene homopolymer (H-PP2) and
[0185] (b) Ethylene propylene rubber (EPR).
[0186] As will be explained in more detail below, the heterophasic propylene copolymer (HECO) according to this invention is produced in the presence of a 4th generation Ziegler-Natta catalyst (see Nello Pasquini, Polypropylene Handbook, 2nd edition, pages 17 and 18). Hence, in contrast to the polypropylene (PP1) which shows a high amount of 2,1 regio defects in the polymer chain, the heterophasic propylene copolymer (HECO) shows no or almost no 2,1 regio defects.
[0187] Thus, the heterophasic propylene copolymer (HECO) according to this invention comprises
[0188] (a) having a pass rate in the range of 0 to less than 0.10% 13 2,1 regio-defective propylene homopolymer (H-PP2) determined by C-NMR spectroscopy, and
[0189] (b) Ethylene propylene rubber (EPR).
[0190] It is especially preferred that the heterophasic propylene copolymer (HECO) according to this invention comprises
[0191] (a) By 13 A propylene homopolymer (H-PP2) in which no 2,1 regio defects can be detected by C-NMR spectroscopy, and
[0192] (b) Ethylene propylene rubber (EPR).
[0193] Additionally it is preferred that the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) similarly to the polypropylene (PP1) also has a broad molecular weight distribution (MWD), i.e. in the range of 5.0 to below 10.0, more preferably in the range of 6.0 to 9.0.
[0194] Thus, in a preferred embodiment the heterophasic propylene copolymer (HECO) according to this invention comprises
[0195] (a) a propylene homopolymer (H-PP2), and
[0196] (b) ethylene propylene rubber (EPR),
[0197] Among them, propylene homopolymer (H-PP2) has
[0198] (i) Pass in the range of 0 to less than 0.10% 13 The 2,1 regio defects determined by C-NMR spectroscopy are preferably determined by 13 C-NMR spectroscopy does not detect 2,1 regio defects, and
[0199] (ii) a molecular weight distribution (MWD) in the range of 5.0 to less than 10.0, preferably in the range of 6.0 to 9.0.
[0200] In order to further improve the properties of the fiber reinforced composite material according to the present invention the molecular weight of the polypropylene (PP1) and the molecular weight of the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) have to be very similar. Accordingly, it is preferred that the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) has a melt flow rate MFR2 (230°C, 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, more preferably in the range of 50.0 to 150 g / 10 min, provided that the melt flow ratio MFR2 between the polypropylene (PP1) and the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) [MFR2(PP1) / MFR2(H-PP2)] is in the range of 0.75 to 1.25, more preferably in the range of 0.80 to 1.20.
[0201] Thus, in a specific preferred embodiment the heterophasic propylene copolymer (HECO) according to this invention comprises
[0202] (a) a propylene homopolymer (H-PP2), and
[0203] (b) ethylene propylene rubber (EPR),
[0204] Among them, propylene homopolymer (H-PP2) has
[0205] (i) Pass in the range of 0 to less than 0.10% 13 The 2,1 regio defects determined by C-NMR spectroscopy are preferably determined by 13 C-NMR spectroscopy does not detect 2,1 regio defects.
[0206] (ii) a molecular weight distribution (MWD) in the range of 5.0 to less than 10.0, preferably in the range of 6.0 to 9.0, and
[0207] (iii) a melt flow rate MFR2 (230°C, 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, more preferably in the range of 50.0 to 150 g / 10 min, provided that the melt flow ratio MFR2 between the polypropylene (PP1) and the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) [MFR2(PP1) / MFR2(H-PP2)] is in the range of 0.75 to 1.25, more preferably in the range of 0.80 to 1.20.
[0208] The propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) may further be characterized by a high melting temperature which is typical for propylene homopolymers obtained by 4th generation Ziegler-Natta catalysts, i.e. a melting temperature of at least 160 °C, more preferably at least 163 °C, like in the range of 163 to 167 °C.
[0209] Accordingly, it is preferred that the heterophasic propylene copolymer (HECO) according to this invention comprises
[0210] (a) a propylene homopolymer (H-PP2), and
[0211] (b) ethylene propylene rubber (EPR),
[0212] Among them, propylene homopolymer (H-PP2) has
[0213] (i) a melting temperature as determined by differential scanning calorimetry (DSC) of at least 160°C, more preferably at least 163°C, such as in the range of 163 to 167°C,
[0214] (ii) Pass in the range of 0 to less than 0.10% 13 The 2,1 regio defects determined by C-NMR spectroscopy are preferably determined by 13 C-NMR spectroscopy does not detect 2,1 regio defects.
[0215] (iii) a molecular weight distribution (MWD) in the range of 5.0 to less than 10.0, preferably in the range of 6.0 to 9.0, and
[0216] (iv) optionally, a melt flow rate MFR2 (230°C, 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, more preferably in the range of 50.0 to 150 g / 10 min, with the proviso that the melt flow ratio MFR2 between the polypropylene (PP1) and the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) [MFR2(PP1) / MFR2(H-PP2)] is in the range of 0.75 to 1.25, more preferably in the range of 0.80 to 1.20.
[0217] Additionally, the heterophasic propylene copolymer (HECO) can be further defined by its elastomeric part, i.e. by the ethylene-propylene rubber (EPR). As known to the skilled person, for a heterophasic system where the matrix is a propylene homopolymer and the elastomeric part is an ethylene-propylene rubber (EPR), the xylene soluble fraction (XCS) reflects the rubber, while the propylene homopolymer (H-PP2) is reflected by the xylene insoluble fraction.
[0218] Accordingly it is preferred that the heterophasic propylene copolymer (HECO) according to this invention has a xylene cold soluble (XCS) content measured according to ISO 16152 at 25 °C in the range of 22 to 45 wt.-%, more preferably in the range of 25 to 40 wt.-%.
[0219] Further, it is preferred that the ethylene content of the xylene cold soluble fraction is rather high. Thus, in a preferred embodiment the heterophasic propylene copolymer (HECO) has an ethylene content in the range of 40 to 60 mol%, more preferably in the range of 48 to 58 mol%. 13 Ethylene content of the xylene cold soluble (XCS) fraction determined by C-NMR.
[0220] Furthermore, the molecular weight of the ethylene-propylene rubber (EPR) of the heterophasic propylene copolymer preferably should not be too low. Accordingly, it is preferred that the xylene cold soluble (XCS) fraction of the heterophasic propylene copolymer (HECO) has an intrinsic viscosity (IV) measured according to ISO 1628 / 1 (in decalin at 135°C) in the range of 2.0 to 5.0 dl / g, preferably in the range of 2.0 to 3.5 dl / g.
[0221] Finally, it is preferred that the heterophasic propylene copolymer (HECO) has in the range of 15 to 33 mol%, more preferably in the range of 20 to 30 mol%. 13 Ethylene content determined by C-NMR, and / or melt flow rate MFR2 (230°C, 2.16 kg) measured according to ISO 1133 in the range of 10 to 50 g / 10 min, more preferably in the range of 15 to 40 g / 10 min.
[0222] Accordingly, it is especially preferred that the heterophasic propylene copolymer (HECO) according to this invention comprises
[0223] (a) a propylene homopolymer (H-PP2), and
[0224] (b) ethylene propylene rubber (EPR),
[0225] wherein the heterophasic propylene copolymer (HECO) has a xylene cold soluble (XCS) content determined according to ISO 16152 at 25 °C in the range of 22 to 45 wt.-%, more preferably in the range of 25 to 40 wt.-%,
[0226] Wherein still further, the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) has
[0227] (i) Pass in the range of 0 to less than 0.10% 13 The 2,1 regio defects determined by C-NMR spectroscopy are preferably determined by 13 C-NMR spectroscopy does not detect 2,1 regio defects.
[0228] (ii) a molecular weight distribution (MWD) in the range of 5.0 to less than 10.0, preferably in the range of 6.0 to 9.0, and
[0229] (iii) optionally, a melt flow rate MFR2 (230°C, 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, more preferably in the range of 50.0 to 150 g / 10 min, provided that the melt flow ratio MFR2 between the polypropylene (PP1) and the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) [MFR2(PP1) / MFR2(H-PP2)] is in the range of 0.75 to 1.25, more preferably in the range of 0.80 to 1.20.
[0230] Still more preferably the heterophasic propylene copolymer (HECO) according to this invention comprises
[0231] (a) a propylene homopolymer (H-PP2), and
[0232] (b) ethylene propylene rubber (EPR),
[0233] wherein the heterophasic propylene copolymer (HECO) has a xylene cold soluble (XCS) content determined according to ISO 16152 at 25 °C in the range of 22 to 45 wt.-%, preferably in the range of 25 to 40 wt.-%,
[0234] The xylene cold soluble (XCS) fraction of the heterophasic propylene copolymer (HECO) has
[0235] (i) in the range of 40 to 60 mol %, more preferably in the range of 48 to 58 mol % 13 Ethylene content determined by C-NMR,
[0236] Wherein still further, the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) has
[0237] (i) Pass in the range of 0 to less than 0.10% 13 The 2,1 regio defects determined by C-NMR spectroscopy are preferably determined by 13 C-NMR spectroscopy does not detect 2,1 regio defects.
[0238] (ii) a molecular weight distribution (MWD) in the range of 5.0 to less than 10.0, preferably in the range of 6.0 to 9.0, and
[0239] (iii) optionally, a melt flow rate MFR2 (230°C, 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, more preferably in the range of 50.0 to 150 g / 10 min, provided that the melt flow ratio MFR2 between the polypropylene (PP1) and the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) [MFR2(PP1) / MFR2(H-PP2)] is in the range of 0.75 to 1.25, more preferably in the range of 0.80 to 1.20.
[0240] Still yet more preferably the heterophasic propylene copolymer (HECO) according to this invention comprises
[0241] (a) a propylene homopolymer (H-PP2), and
[0242] (b) ethylene propylene rubber (EPR),
[0243] wherein the heterophasic propylene copolymer (HECO) has a xylene cold soluble (XCS) content determined according to ISO 16152 at 25 °C in the range of 22 to 45 wt.-%, preferably in the range of 25 to 40 wt.-%,
[0244] wherein further the xylene cold soluble (XCS) fraction of the heterophasic propylene copolymer (HECO) has
[0245] (i) in the range of 40 to 60 mol %, more preferably in the range of 48 to 58 mol % 13 Ethylene content determined by C-NMR, and
[0246] (ii) an intrinsic viscosity (IV) measured according to ISO 1628 / 1 (in decalin at 135° C.) in the range of 2.0 to 5.0 dl / g, preferably in the range of 2.0 to 3.5 dl / g,
[0247] Wherein still further, the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) has
[0248] (i) a melting temperature as measured by differential scanning calorimetry (DSC) of at least 160°C, more preferably at least 163°C,
[0249] (ii) Pass in the range of 0 to less than 0.10% 13 The 2,1 regio defects determined by C-NMR spectroscopy are preferably determined by 13 C-NMR spectroscopy does not detect 2,1 regio defects.
[0250] (iii) a molecular weight distribution (MWD) in the range of 5.0 to less than 10.0, preferably in the range of 6.0 to 9.0, and
[0251] (iv) optionally, a melt flow rate MFR2 (230°C, 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, more preferably in the range of 50.0 to 150 g / 10 min, with the proviso that the melt flow ratio MFR2 between the polypropylene (PP1) and the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) [MFR2(PP1) / MFR2(H-PP2)] is in the range of 0.75 to 1.25, more preferably in the range of 0.80 to 1.20.
[0252] Even yet more preferably, the heterophasic propylene copolymer (HECO) according to this invention comprises
[0253] (a) a propylene homopolymer (H-PP2), and
[0254] (b) ethylene propylene rubber (EPR),
[0255] The heterophasic propylene copolymer (HECO) has
[0256] (i) in the range of 15 to 33 mol %, more preferably in the range of 20 to 30 mol % 13 Ethylene content determined by C-NMR,
[0257] (ii) a melt flow rate MFR2 (230°C, 2.16 kg) measured according to ISO 1133 in the range of 10 to 50 g / 10 min, more preferably in the range of 15 to 40 g / 10 min,
[0258] wherein further the heterophasic propylene copolymer (HECO) has a xylene cold soluble (XCS) content measured according to ISO 16152 at 25 °C in the range of 22 to 45 wt.-%, preferably in the range of 25 to 40 wt.-%,
[0259] wherein still further the xylene cold soluble (XCS) fraction of the heterophasic propylene copolymer (HECO) has
[0260] (i) in the range of 40 to 60 mol %, more preferably in the range of 48 to 58 mol % 13 Ethylene content determined by C-NMR, and
[0261] (ii) an intrinsic viscosity (IV) measured according to ISO 1628 / 1 (in decalin at 135° C.) in the range of 2.0 to 5.0 dl / g, preferably in the range of 2.0 to 3.5 dl / g,
[0262] Wherein still further, the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) has
[0263] (i) a melting temperature as measured by differential scanning calorimetry (DSC) of at least 160°C, more preferably at least 163°C,
[0264] (ii) Pass in the range of 0 to less than 0.10% 13 The 2,1 regio defects determined by C-NMR spectroscopy are preferably determined by 13 C-NMR spectroscopy does not detect 2,1 regio defects.
[0265] (iii) a molecular weight distribution (MWD) in the range of 5.0 to less than 10.0, preferably in the range of 6.0 to 9.0, and
[0266] (iv) optionally, a melt flow rate MFR2 (230°C, 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, more preferably in the range of 50.0 to 150 g / 10 min, with the proviso that the melt flow ratio MFR2 between the polypropylene (PP1) and the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) [MFR2(PP1) / MFR2(H-PP2)] is in the range of 0.75 to 1.25, more preferably in the range of 0.80 to 1.20.
[0267] As mentioned above, the heterophasic propylene copolymer (HECO) according to the present invention is produced using a 4th generation Ziegler-Natta catalyst. Such catalysts are prior art and well known to the skilled person. For example as Ziegler-Natta catalyst the BHC01P catalyst of Borealis can be used (prepared according to WO 92 / 19653, as disclosed in WO 99 / 24479; in particular using dioctyl phthalate as dialkyl phthalate of formula (I) according to WO 92 / 19658) or the commercially available catalyst Polytrack 8502 from Grace can be used (WO 92 / 19658 and WO 92 / 19653).
[0268] The polymerization conditions for producing the heterophasic propylene copolymer (HECO) are also known to the skilled person. The heterophasic propylene copolymer (HECO) is produced in two polymerization zones, in the first zone a propylene homopolymer (H-PP2) is produced, and in the second polymerization zone an ethylene-propylene rubber (EPR) is obtained. Each zone may comprise one or more reactors. For example, the first zone may contain only a loop reactor, while the second zone may contain only one gas phase reactor. However, it is preferred that the first zone contains a loop reactor and a gas phase reactor, while the second zone contains two gas phase reactors.
[0269] Thus, the process for preparing the heterophasic propylene copolymer (HECO) according to this invention is preferably a sequential polymerization process comprising at least two, preferably four reactors connected in series, wherein the process comprises the following steps
[0270] (A) polymerizing propylene in a first reactor (R-1), the first reactor (R-1) being a slurry reactor (SR), preferably a loop reactor (LR), to obtain a first fraction of propylene homopolymer (H-PP2) as defined in the present invention,
[0271] (B) transferring said first fraction of the propylene homopolymer (H-PP2) from the first reactor (R-1) to a second reactor (R-2), the second reactor (R-2) being a gas phase reactor (GPR-1),
[0272] (C) feeding propylene into the second reactor (R-2),
[0273] (D) polymerizing propylene in the presence of the first fraction of propylene homopolymer (H-PP2) in the second reactor (R-2) to obtain a second fraction of propylene homopolymer (H-PP2), said first and second fractions forming the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO),
[0274] (E) transferring the propylene homopolymer (H-PP2) of the second reactor (R-2) to a third reactor (R-3), the third reactor being a gas phase reactor (GPR-2),
[0275] (F) feeding propylene and ethylene into the third reactor (R-3),
[0276] (G) polymerizing propylene and ethylene in the presence of the propylene homopolymer (H-PP2) in the third reactor (R-3) to obtain a first fraction of ethylene-propylene rubber (EPR),
[0277] (H) transferring the mixture of the propylene homopolymer (H-PP2) and the first fraction of the ethylene-propylene rubber (EPR) from the third reactor (R-3) to a fourth reactor (R-4), the fourth reactor (R-4) being a gas phase reactor (GPR-3),
[0278] (I) feeding propylene and ethylene into the fourth reactor (R-4),
[0279] (J) polymerizing propylene and ethylene in the presence of the mixture from the third reactor (R-3) in the fourth reactor (R-4) to obtain a second fraction of ethylene-propylene rubber (EPR),
[0280] The first fraction and the second fraction of ethylene propylene rubber (EPR) form ethylene propylene rubber (EPR), and
[0281] The propylene homopolymer (H-PP2) and the ethylene-propylene rubber (EPR) form a heterophasic propylene copolymer (HECO), wherein further
[0282] In the first reactor (R-1), the second reactor (R-2), the third reactor (R-3) and the fourth reactor (R-4), polymerization takes place in the presence of a 4th generation Ziegler-Natta catalyst.
[0283] A preferred multi-stage process is a "loop-gas phase" process such as that developed by Borealis A / S of Denmark (known as Technology) is described, for example, in patent literature, such as EP 0 887 379 or WO 92 / 12182.
[0284] Heterophasic polymers can be produced according to various processes, for example as described in WO 92 / 12182, EP 0 887 379 and WO 98 / 58976. The contents of these documents are included herein by reference.
[0285] Preferably, in the inventive process for the production of a heterophasic propylene copolymer (HECO) as defined above, the conditions for the first reactor (R-1), i.e. the slurry reactor (SR), like the loop reactor (LR), in step (A) may be as follows:
[0286] - a temperature in the range of 40°C to 110°C, preferably between 60°C and 100°C, more preferably in the range of 65 to 90°C,
[0287] - a pressure in the range of 20 to 80 bar, preferably between 40 and 70 bar,
[0288] - Hydrogen can be added in a manner known per se to control the molar mass.
[0289] Subsequently, the reaction mixture of step (A) is transferred to the second reactor (R-2), i.e. the gas phase reactor (GPR-1), i.e. to step (D), wherein the conditions in step (D) are preferably as follows:
[0290] - a temperature in the range of 50°C to 130°C, preferably between 60°C and 100°C,
[0291] - a pressure in the range of 5 to 50 bar, preferably between 15 and 40 bar,
[0292] - Hydrogen can be added in a manner known per se to control the molar mass.
[0293] The residence time in the two reactor zones can vary.
[0294] In one embodiment of the process for producing the heterophasic polypropylene composition (HECO), the residence time in the slurry reactor (SR), e.g. the loop (LR), is in the range of 0.2 to 2.5 hours, such as in the range of 0.3 to 1.5 hours and the residence time in the first gas phase reactor (GPR-1) is typically in the range of 0.2 to 4.0 hours, such as 0.5 to 3.0 hours.
[0295] If desired, the polymerization can be carried out in a known manner in the first reactor (R-1), ie a slurry reactor (SR), such as a loop reactor (LR), under supercritical conditions.
[0296] The conditions in the third reactor (R-3), i.e. the second gas phase reactor (GPR-2) and any other subsequent gas phase reactors (GPR) (if present) are similar to those in the second reactor (R-2). In addition, the residence time in the second and third gas phase reactors (GPR-2 and GPR-3) is in the same range or higher than the residence time in the first gas phase reactor (GPR-1).
[0297] The process may also comprise a prepolymerization prior to the polymerization in the first reactor (R-1). The prepolymerization may be carried out in the first reactor (R-1), however it is preferred that the prepolymerization takes place in a separate reactor, the so-called prepolymerization reactor.
[0298] Fiberglass
[0299] The third mandatory component in the fiber reinforced composite material is glass fiber. The glass fiber can be any type of glass fiber, such as long glass fiber or short glass fiber. However, it is particularly preferred that the glass fiber is short glass fiber, also known as cut glass fiber or chopped glass strand (strand, or raw filament).
[0300] The short glass fibers used in the fiber-reinforced composite material preferably have an average fiber length before compounding in the range of 2.0 to 10.0 mm, more preferably in the range of 2.0 to 8.0 mm, still more preferably in the range of 2.0 to 5.0 mm.
[0301] It is further preferred that the short glass fibers used in the fiber-reinforced composite material preferably have an average diameter of from 5 to 20 μm, more preferably from 8 to 18 μm, still more preferably 8 to 15 μm before compounding.
[0302] Preferably, the short glass fibers have an aspect ratio (also called aspect ratio), defined as the ratio between the average fiber length and the average fiber diameter, of 150 to 600, preferably 200 to 500, more preferably 250 to 400 before compounding. The aspect ratio is the relationship between the average length and the average diameter of the fiber.
[0303] Compatibilizer
[0304] Another component present in fiber reinforced composites is a compatibilizer, or also known as a coupling agent or adhesion promoter. The compatibilizer improves the adhesion between the non-polar polypropylene and the polar glass fibers.
[0305] The compatibilizer according to the present invention is preferably a polar modified polypropylene. The polar modified polypropylene, such as a polar modified propylene homopolymer or a polar modified copolymer, has a high degree of compatibility with the polypropylene of the fiber reinforced composite material according to the present invention.
[0306] From a structural point of view, the polar modified polypropylene is preferably selected from graft or block copolymers.
[0307] In this context, preference is given to polar modified polypropylenes which contain groups which originate from polar compounds, in particular selected from the group consisting of anhydrides, carboxylic acids, carboxylic acid derivatives, primary and secondary amines, hydroxyl compounds, oxazolines and epoxides and also ionic compounds.
[0308] Specific examples of the polar compounds are unsaturated cyclic anhydrides and aliphatic diesters thereof, and diacid derivatives. In particular, one can use maleic anhydride and a C1 to C 10 Straight chain and branched dialkyl maleates, C1 to C 10 Straight chain and branched dialkyl fumarate, itaconic anhydride, C1 to C 10 Compounds of linear and branched dialkyl itaconates, maleic acid, fumaric acid, itaconic acid and mixtures thereof.
[0309] In a particularly preferred embodiment of the present invention, the polar modified polypropylene is maleic anhydride grafted polypropylene, wherein the polypropylene is a propylene-ethylene copolymer or a propylene homopolymer. It is particularly preferred that the polar modified polypropylene is maleic anhydride grafted polypropylene, wherein the polypropylene is a propylene homopolymer.
[0310] Polar modified polypropylene, in particular maleic anhydride grafted polypropylene, can be produced in a simple manner by reactive extrusion of polypropylene, for example with maleic anhydride in the presence of a free radical generator, such as an organic peroxide, as disclosed in EP 0 572 028, for example.
[0311] The amount of the groups derived from the polar compound, such as maleic anhydride, in the polar modified polypropylene is 0.1 to 5.0 wt%, preferably 0.5 to 4.0 wt%, more preferably 0.5 to 3.0 wt%.
[0312] Preferably, the polar modified polypropylene (like maleic anhydride grafted polypropylene) has a melt flow rate MFR2 (190°C, 2.16 kg) measured according to ISO 1133 of at least 50 g / 10 min, more preferably at least 80 g / 10 min, yet more preferably in the range of 50 to 500 g / 10 min, still yet more preferably in the range of 70 to 250 g / 10 min.
[0313] additive
[0314] The fiber-reinforced composite material according to the present invention may further include additives. Typical additives are acid scavengers, antioxidants, colorants, light stabilizers, slip agents, anti-scratch agents, dispersants, processing aids, lubricants, pigments (e.g. carbon black) and the like.
[0315] Such additives are commercially available and are described, for example, in “Plastic Additives Handbook” by Hans Zweifel, 6th edition, 2009 (pp. 1141 to 1190).
[0316] Additives are usually provided in the form of masterbatches. A masterbatch is a composition in which a considerable amount of an additive or a mixture of additives is dispersed in a polymer. Therefore, the term "additive" according to the present invention also includes a carrier material, in particular a polymer carrier material, in which the "active additive" or "mixture of active additives" is dispersed.
[0317] Process for producing fiber-reinforced composite materials
[0318] The production of reinforced fiber composite materials is well known in the art. Thus, a fiber reinforced composite material is manufactured by a process comprising the steps of adding the following components into an extruder and extruding them to obtain said fiber reinforced composite material
[0319] (a) Polypropylene (PP1),
[0320] (b) a heterophasic propylene copolymer (HECO),
[0321] (c) glass fibers,
[0322] (d) a compatibilizer, and
[0323] (e) Optional additives.
[0324] For the extrusion of each component of the composite material, i.e. melt blending, conventional compounding or blending devices can be used, such as Banbury mixer, double roll rubber mill, Buss co-kneader or twin screw extruder. The fiber reinforced composite material recovered from the extruder / mixer is generally in the form of particles. These particles are then preferably further processed, such as by injection molding to generate the articles and products of the composite material of the present invention.
[0325] It is particularly preferred that the fiber-reinforced composite material according to the invention is produced by melt blending the individual components in an extruder, preferably a twin-screw extruder.
[0326] In particular, it is preferred that the fiber-reinforced composite material according to the present invention is obtained by a process comprising the following steps:
[0327] (a) feeding the polypropylene (PP1), the heterophasic propylene copolymer (HECO), the compatibilizer (CA) and optionally additives (AD) into an extruder, preferably a twin screw extruder,
[0328] (b) melt-kneading the composition obtained in step (a) at a temperature of 200 to 270° C.,
[0329] (c) feeding (short) glass fibers (GF) into an extruder, preferably a twin-screw extruder, containing the composition obtained in step (b), and
[0330] (d) melt-kneading the composition obtained in step (c) at a temperature of 200 to 270° C., thereby obtaining a fiber-reinforced composite material.
[0331] Products
[0332] The present invention further relates to an article, preferably an automotive article, comprising at least 95 wt. %, more preferably at least 98 wt. %, still more preferably consisting of a fiber reinforced composite material according to the present invention.
[0333] Particularly preferred embodiments
[0334] Particularly preferred embodiments are as follows:
[0335] [1] Fiber-reinforced composite materials, including
[0336] (a) based on a fiber-reinforced composite material, 30 to 60 wt. % of a polypropylene (PP1),
[0337] (b) 10 to 40 wt.-%, based on the fiber reinforced composite, of a heterophasic propylene copolymer (HECO), wherein the heterophasic propylene copolymer (HECO) comprises a propylene homopolymer (H-PP2) and an ethylene-propylene rubber (EPR),
[0338] (c) based on the fiber-reinforced composite material, 10 to 40 wt.% of glass fiber (GF), and
[0339] (d) 0.05 to 5.0 wt. % of a compatibilizer (CA), based on the fiber-reinforced composite material,
[0340] The total amount of the polypropylene (PP1), the heterophasic propylene copolymer (HECO), the glass fibers (GF) and the compatibilizer (CA) in the fiber reinforced composite material is at least 95 wt.%,
[0341] wherein further, the polypropylene (PP1) has
[0342] (i) a melt flow rate MFR2 (230° C., 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min,
[0343] (ii) not more than 0.5% by weight 13 The comonomer content was determined by C-NMR spectroscopy. The comonomer was ethylene.
[0344] (iii) a molecular weight distribution (MWD) as determined by gel permeation chromatography (GPC) in the range of greater than 4.5 to less than 8.5, and
[0345] (iv) Pass in the range of 0.20 to 1.00% 13 2,1 regio defects determined by C-NMR spectroscopy,
[0346] Wherein still further, the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) has
[0347] (v) Pass in the range of 0 to less than 0.10% 13 2,1 regiodefects determined by C-NMR spectroscopy.
[0348] [2] The fiber-reinforced composite material according to embodiment [1], wherein the fiber-reinforced composite material has a melt flow rate MFR2 (230° C., 2.16 kg) measured according to ISO 1133 in the range of 8.0 to 50 g / 10 min.
[0349] [3] A fiber reinforced composite material according to embodiment [1] or [2], wherein the glass fibers are embedded in a continuous phase comprising at least 98 wt.-% of a mixture of a polypropylene (PP1) and a heterophasic propylene copolymer (HECO).
[0350] [4] A fiber reinforced composite material according to any of embodiments [1] to [3], wherein the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) has a melt flow rate MFR2 (230°C, 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, provided that the melt flow ratio MFR2 between the polypropylene (PP1) and the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) [MFR2(PP1) / MFR2(H-PP2)] is in the range of 0.80 to 1.20.
[0351] [5] A fiber-reinforced composite material according to any one of embodiments [1] to [4], wherein the weight ratio between the mixture of polypropylene (PP1) and propylene homopolymer (H-PP2) and the ethylene-propylene rubber (EPR) [((PP1)+(H-PP2) / (EPR)] is in the range of 75:25 to 95:5.
[0352] [6] A fiber reinforced composite material according to any of the preceding embodiments [1] to [5], wherein the weight ratio between the polypropylene (PP1) and the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) [(PP1) / (H-PP2)] is in the range of 60:40 to 80:20.
[0353] [7] A fiber reinforced composite material according to any of the preceding embodiments [1] to [6], wherein the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) has a molecular weight distribution (MWD) as determined by gel permeation chromatography (GPC) in the range of more than 5.0 to less than 10.0.
[0354] [8] A fiber reinforced composite material according to any of the preceding embodiments [1] to [7], wherein the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) has a melting temperature Tm as measured according to differential scanning calorimetry (DSC) of at least 160 °C.
[0355] [9] The fiber reinforced composite material according to any of the preceding embodiments [1] to [8], wherein the heterophasic propylene copolymer (HECO) has a melt flow rate MFR2 (230°C, 2.16 kg) measured according to ISO 1133 in the range of 10 to 50 g / 10 min.
[0356]
[10] The fiber reinforced composite material according to any of the preceding embodiments [1] to [9], wherein the heterophasic propylene copolymer (HECO) has a xylene cold soluble (XCS) content in the range of 22 to 45 wt.-%, measured according to ISO 16152 at 25 °C.
[0357]
[11] The fiber reinforced composite material according to any of the preceding embodiments [1] to
[10] , wherein the heterophasic propylene copolymer (HECO) has a xylene cold soluble (XCS) fraction in the range of 40 to 60 mol%. 13 Ethylene content measured by C-NMR.
[0358]
[12] The fiber reinforced composite material according to any of the preceding embodiments [1] to
[11] , wherein the heterophasic propylene copolymer (HECO) has an ethylene content in the range of 15 to 33 mol%.
[0359]
[13] A fiber reinforced composite material according to any of the preceding embodiments [1] to
[12] , wherein the xylene cold soluble (XCS) fraction of the heterophasic propylene copolymer (HECO) has an intrinsic viscosity (IV) measured according to ISO 1628 / 1 (in decalin at 135 °C) in the range of 2.0 to 5.0 dl / g.
[0360]
[14] The fiber reinforced composite material according to any of the preceding embodiments [1] to
[13] , wherein the heterophasic propylene copolymer (HECO) is non-visbroken.
[0361]
[15] The fiber-reinforced composite material according to any one of the preceding embodiments [1] to
[14] , wherein the polypropylene (PP1) has a fraction eluting at less than 100°C by temperature rising elution fractionation (TREF) in the range of 12 to 20 wt%.
[0362]
[16] The fiber-reinforced composite material according to any one of the preceding embodiments [1] to
[15] , wherein the polypropylene (PP1) is a propylene homopolymer.
[0363]
[17] The fiber-reinforced composite material according to any one of the preceding embodiments [1] to
[16] , wherein the polypropylene (PP1) is non-visbroken.
[0364]
[18] The fiber-reinforced composite material according to any of the preceding embodiments [1] to
[18] , wherein the polypropylene (PP1) has a melting temperature Tm in the range of 150 to 159°C as measured by differential scanning calorimetry (DSC).
[0365]
[19] The fiber reinforced composite material according to any of the preceding embodiments [1] to
[19] , wherein the polypropylene (PP1) has a xylene cold soluble (XCS) content in the range of 0.8 to 2.5 wt.-%, measured at 25°C according to ISO 16152.
[0366]
[20] The fiber-reinforced composite material according to any one of the preceding embodiments [1] to
[19] , wherein the polypropylene (PP1) is produced by polymerizing propylene and optionally ethylene in the presence of a metallocene catalyst having formula (I):
[0367]
[0368] Each R 1 are independently the same or different and are hydrogen or a linear or branched C1-C6 alkyl group, wherein at least one R of each phenyl group 1 Not hydrogen,
[0369] R' is C1-C 10 A hydrocarbon group, preferably a C1-C4 hydrocarbon group, more preferably a methyl group, and
[0370] X is independently a hydrogen atom, a halogen atom, a C1-C6 alkoxy group, a C1-C6 alkyl group, a phenyl group or a benzyl group.
[0371]
[21] The fiber-reinforced composite material according to any one of the aforementioned embodiments [1] to
[20] , wherein the glass fiber (GF) is a short glass fiber.
[0372]
[22] The fiber-reinforced composite material according to embodiment
[21] , wherein the glass fiber (GF) has an average fiber length of 2.0 to 10.0 mm and optionally an average diameter of 5 to 20 μm before compounding.
[0373]
[23] The fiber-reinforced composite material according to any one of the aforementioned embodiments [1] to
[22] , wherein the compatibilizer (CA) is a polar-modified polypropylene, preferably a maleic anhydride-grafted polypropylene.
[0374]
[24] A fiber-reinforced composite material according to embodiment
[23] , wherein the maleic anhydride grafted polypropylene has a maleic anhydride content of 0.1 to 5.0 wt. %, and a melt flow rate MFR2 (190°C, 2.16 kg) measured according to ISO 1133 of preferably at least 70 g / 10 min, more preferably in the range of 80 to 250 g / 10 min.
[0375]
[25] The fiber-reinforced composite material according to any one of the aforementioned embodiments [1] to
[24] , wherein the fiber-reinforced composite material consists of the following
[0376] (a) based on a fiber-reinforced composite material, 35 to 55 wt. % of a polypropylene (PP1),
[0377] (b) 20 to 35 wt.-% of a heterophasic propylene copolymer (HECO), based on the fiber-reinforced composite material,
[0378] (c) based on fiber-reinforced composite materials, 15 to 30 wt. % of glass fibers (GF),
[0379] (d) 0.5 to 5.0 wt. % of a compatibilizer (CA), based on the fiber-reinforced composite material, and
[0380] (e) 0.1 to 5.0 wt. % of additives, based on the fiber-reinforced composite material.
[0381] The present invention will now be described by way of examples.
[0382] Example
[0383] A. Determination Method
[0384] Unless otherwise defined, the following definitions of terms and determination methods apply to the above general description of the invention including the claims, as well as to the following examples.
[0385] Quantification of microstructure by NMR spectroscopy
[0386] Quantitative nuclear magnetic resonance (NMR) spectroscopy was used to quantify the isotacticity and regioregularity of the ethylene-propylene copolymers.
[0387] Use for 1 H and 13 Quantitative measurements were recorded in solution on a Bruker Advance III 400 NMR spectrometer operating at 400.15 and 100.62 MHz, respectively. 13 C{ 1 H} NMR spectroscopy. Nitrogen was used for all pneumatics and all spectra were 13 C-optimized 10 mm extended temperature probe recorded at 125 °C.
[0388] Approximately 200 mg of material was dissolved in 1,2-tetrachloroethane-d2 (TCE-d2). To ensure a homogeneous solution, the NMR tube was further heated in a rotary oven for at least 1 hour after initial sample preparation in a heating block. After insertion into the magnet, the tube was rotated at 10 Hz. This setting was chosen primarily for the high resolution required for quantification of stereoregularity distribution (Busico, V., Cipullo, R., Prog. Polym. Sci. 26 (2001) 443; Busico, V.; Cipullo, R., Monaco, G., Vacatello, M., Segre, AL, Macromolecules 30 (1997) 6251). Standard single pulse excitation was used, using NOE and a two-stage WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D. Winniford, B., J. Mag. Reson. 187 (2007) 225; Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 11289). A total of 8192 (8k) transient values were collected for each spectrum.
[0389] Quantification was performed using a dedicated computer program 13 C{ 1 H} NMR spectra are processed, integrated, and relevant quantitative properties are determined from the integrals.
[0390] All chemical shifts were internally referenced to the methyl isotactic pentad (mmmm) at 21.85 ppm.
[0391] Characteristic signals corresponding to regio defects (Resconi, L., Cavallo, L., Fait, A., Piemontesi, F., Chem. Rev. 2000, 100, 1253; Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157; Cheng, HN, Macromolecules 17 (1984), 1950) or comonomers were observed.
[0392] The stereoregularity distribution is quantified by integrating the methyl region between 23.6 and 19.7 ppm, correcting for any sites not associated with the stereo sequence of interest (Busico, V., Cipullo, R., Prog. Polym. Sci. 26 (2001) 443; Busico, V., Cipullo, R., Monaco, G., Vacatello, M., Segre, AL, Macromolecules 30 (1997) 6251).
[0393] Specifically, the quantitative effects of regio defects and comonomers on the tacticity distribution were corrected by subtracting representative regio defect and comonomer integrals from a specific integrated region of the stereo sequence.
[0394] Isotacticity is determined at the pentad level and is reported as the percentage of isotactic pentad (mmmm) sequences relative to all pentad sequences:
[0395] [mmmm]% = 100*(mmmm / sum of all pentads)
[0396] The presence of the 2,1 erythro regio defect is indicated by the presence of two methyl sites at 17.7 and 17.2 ppm and confirmed by other characteristic sites. No characteristic signals corresponding to other types of regio defects were observed (Resconi, L., Cavallo, L., Fait, A., Piemontesi, F., Chem. Rev. 2000, 100, 1253).
[0397] The amount of 2,1-erythro regiodefects was quantified using the average integral of the two characteristic methyl sites at 17.7 and 17.2 ppm:
[0398] P 21e =(I e6 +I e8 ) / 2
[0399] 1,2 The amount of primary insertion propene was quantified based on the methyl region and corrections were made for sites not involved in the primary insertion and for primary insertion sites not included in the region:
[0400] P 12 =I CH3 +P 12e
[0401] The total amount of propene is quantified as the sum of the primary inserted propene and all other regio defects present:
[0402] P 总 =P 12 +P 21e
[0403] The mole percentage of 2,1 erythro regio defects relative to all propylene is quantified:
[0404] [21e] mol% = 100*(P 21e / P 总 )
[0405] The method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157) was used to 13 C{ 1 The comonomer fraction is quantified by integrating multiple signals over the entire spectral area in the H} spectrum. This approach was chosen for its robustness and ability to account for the presence of regio defects when required. The integration area was slightly adjusted to improve applicability over the entire range of comonomer content encountered.
[0406] For systems where only isolated ethylene in the PPEPP sequence is observed, the method of Wang et al. was modified to reduce the effect of non-zero integrals at sites known to be absent. This approach reduces the overestimation of ethylene content in such systems and is achieved by reducing the number of sites used to determine absolute ethylene content to:
[0407] E=0.5(S ββ +S βγ +S βδ +0.5(S αβ +S αγ )).
[0408] Using this set of sites, the corresponding integral equation becomes:
[0409] E=0.5(I H +I G +0.5(I C +I D ))
[0410] The same symbols used in the article by Wang et al. are used (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157). The equations for absolute propylene content are not modified.
[0411] Calculate the mole percentage of comonomer incorporation from the mole fraction:
[0412] E[mol%]=100*f E .
[0413] Calculate the weight percent comonomer incorporation from the mole fractions:
[0414] E[wt%]=100*(f E *28.06) / ((f E *28.06)+((1-f E )*42.08)).
[0415] Melt flow rate
[0416] The melt flow rate (MFR) is determined according to ISO 1133 and is expressed in g / 10 min. The MFR indicates the fluidity and, therefore, the processability of a polymer. The higher the melt flow rate, the lower the viscosity of the polymer. The MFR2 of polypropylene is determined at a temperature of 230°C and a load of 2.16 kg.
[0417] Calculate the melt flow rate MFR2 (230°C) of the polypropylene produced in the first gas phase reactor (GPR1):
[0418]
[0419] in
[0420] w(PP1) is the weight fraction [in wt. %] of the polypropylene fraction produced in the loop reactor and the prepolymerization reactor, w(PP2) is the weight fraction [in wt. %] of the polypropylene fraction produced in the first gas phase reactor (GPR1),
[0421] MFR(PP1) is the melt flow rate MFR2 (230°C) of the polypropylene fraction withdrawn from the loop reactor in g / 10 min,
[0422] MFR(PP) is the melt flow rate MFR2 (230°C) of the polypropylene taken out from the first gas phase reactor [in g / 10 min],
[0423] MFR(PP2) is the calculated melt flow rate MFR2 (230°C) [in g / 10 min] of the polypropylene fraction produced in the first gas phase reactor (GPR1).
[0424] Molar mass (ethylene-propylene copolymer)
[0425] The molar mass averages (Mz, Mw and Mn) and the molecular weight distribution (MWD) (ie Mw / Mn) were determined by gel permeation chromatography (GPC) according to ISO 16014-4:2003 and ASTM D 6474-99 using the following formula:
[0426]
[0427] where Ai and Mi are the chromatographic peak slice area and the molecular weight (MW) of the polyolefin.
[0428] The PolymerChar GPC instrument equipped with an infrared (IR) detector was used with 3×Olexis and 1×Olexis guard columns from Polymer Laboratories and 1,2,4-trichlorobenzene (TCB, stabilized with 250 mg / l of 2,6-di-tert-butyl-4-methyl-phenol) as solvent at 160°C and at a constant flow rate of 1 ml / min. 200 μL of sample solution was injected per analysis. The column set was calibrated using universal calibration (according to ISO 16014-2:2003) using at least 15 narrow MWD polystyrene (PS) standards in the range of 0.5 kg / mol to 11500 kg / mol. The MarkHouwink constants used for PS, PE and PP are as described according to ASTM D 6474-99. All samples were prepared by dissolving 5.0 to 9.0 mg of polymer in 8 ml (at 160 °C) stabilized TCB (same as mobile phase) in the autosampler of the GPC instrument at 160 °C with constant gentle shaking for 2.5 h (for PP) or 3 h (for PE).
[0429] TREF Method
[0430] Chemical composition distribution is determined by analyzing temperature rising elution fractionation as described by Soares, JBP, Fractionation, in: Encyclopedia Of Polymer Science and Technology, John Wiley & Sons, New York, pp. 75-131, Vol. 10, 2001. The separation of polymers in TREF is carried out according to their crystallinity in solution. TREF distribution curves are generated using a CRYSTAF-TREF 200+ instrument manufactured by PolymerChar SA (Valencia, Spain).
[0431] The polymer sample was dissolved in 1,2,4-trichlorobenzene (TCB, stabilized with 250 mg / L 2,6-di-tert-butyl-4-methyl-phenol) at a concentration between 1.5 and 2.0 mg / ml at 150°C for 180 minutes, and 1.8 mL of the sample solution was injected into a column (8 mm inner diameter, 15 cm length, filled with inert substances such as glass beads). The column oven was then quickly cooled to 110°C and kept at 110°C for 30 minutes for stabilization purposes, and then it was slowly cooled to 35°C at a constant cooling rate (0.1°C / min). The polymer was then eluted from the column at a flow rate of 0.5 ml / min with 1,2,4-trichlorobenzene (stabilized with 250 mg / L 2,6-di-tert-butyl-4-methyl-phenol) at 35°C for a period of 10 min, followed by a temperature increase from 35°C to 135°C at a constant heating rate of 0.5°C / ram and elution at a flow rate of 0.5 ml / min. The concentration of the polymer during elution was recorded by an infrared detector (measurement of CH absorption at a wavelength of 3.5 microns). The detector response was plotted as a function of temperature.
[0432] Normalized concentration curves are presented as fractograms along with the cumulative concentration signal normalized to 100.
[0433] Definition of High Crystalline Fraction (HCF) and Low Crystalline Fraction (LCF):
[0434] The high crystalline fraction (HCF) is the amount in weight % of the polymer fraction eluted at elution temperatures of 100°C and above.
[0435] The low crystalline fraction (LCF) refers to the amount in weight % of the polymer fraction eluted at conditions between 35 and below 100°C.
[0436] Xylene soluble fraction at room temperature (XCS, weight %):
[0437] The amount of polymer soluble in xylene is determined according to ISO 16152; 5th edition; 2005-07-01 at 25°C.
[0438] Intrinsic viscosity: The intrinsic viscosity (IV) is measured according to DIN ISO 1628 / 1, October 1999, at 135°C in decalin.
[0439] DSC analysis, melting temperature (T m ) and melting enthalpy (H m ), crystallization temperature (T c ) and crystallization enthalpy (H c ): Measurements were performed on 5 to 7 mg samples using a TA Instrument Q200 Differential Scanning Calorimetry (DSC). The DSC was run according to ISO 11357 / Part 3 / Method C2 with a heating / cooling / heating cycle in the temperature range of -30 to +225°C at a scanning rate of 10°C / min. The crystallization temperature (T c ) and crystallization enthalpy (H c ) is determined by the cooling step, while the melting temperature (T m ) and melting enthalpy (H m ) is determined by the second heating step.
[0440] Spiral flow length
[0441] Spiral flow length: This method specifies the principle of testing the flowability of plastic materials by using injection molding, taking into account the cooling effect of the mold. The plastic is melted and plasticized by the screw in the hot cylinder. The molten plastic is injected into the cavity at a certain speed and pressure by the piston action of the screw. The cavity is spiral-shaped and the scale for length measurement is printed on the steel. This allows the flow length to be read directly on the injection molded test spiral specimen.
[0442] The spiral tests were carried out using an Engel ES1050 / 250HL injection moulding unit equipped with a spiral mould and a pressure of 1400 bar.
[0443] Screw diameter: 55mm
[0444] Specifications, injection pressure: 1400 bar
[0445] Tool form: round, spiral; length 1545mm; profile: trapezoidal 2.1mm thickness; cross-sectional area 20.16mm 2 Pre-cavity and die temperature: 230℃
[0446] Temperature in Zone 2 / Zone 3 / Zone 4 / Zone 5 / Zone 6: 230°C / 230°C / 220°C / 220°C / 200°C
[0447] Injection cycle: Injection time including holding: 6s
[0448] Cooling time: 10s
[0449] Screw speed: 50mm / sec
[0450] Tool temperature: 40°C
[0451] The spiral flow length can be determined immediately after the injection molding operation.
[0452] Flexural modulus
[0453] Flexural modulus is measured according to ISO 178 Method A (3-point bending test) on a 80×10×4 mm 3 The test results are measured on the test specimens. According to this standard, a test speed of 2 mm / min and a span length of 16 times the thickness are used. The test temperature is 23 ± 2 °C. Injection molding is carried out according to ISO 19069-2, and for all materials a melt temperature of 200 °C is used, regardless of the material melt flow rate.
[0454] Tensile modulus, tensile strength and elongation at break
[0455] Tensile modulus, tensile strength and elongation at break were measured according to ISO 527-2 using injection moulded test specimens as described in EN ISO 1873-2 (1 B dog bone, 4 mm thickness).
[0456] Simply supported beam unnotched impact strength
[0457] According to ISO 179 1eU at +23°C using 80×10×4 mm prepared in the same way as for the flexural modulus 3 Charpy unnotched impact strength measured on injection molded bar test specimens.
[0458] Heat Deflection Temperature (HDT):
[0459] In the same way as the flexural modulus, a 80×10×4 mm 3 HDT is determined on injection moulded test specimens. The test is carried out according to ISO 75, Condition A, using a nominal surface stress of 1.80 MPa on flat supported specimens.
[0460] VOC and FOG
[0461] The VOC and FOG values were measured according to VDA 278 (October 2011; Thermal Desorption Analysis of Organic Emissions for the Characterization of Non-Metallic Materials for Automobiles, VDA Verband der Automobilindustrie) after sample preparation of the injection-molded plates according to EN ISO 19069-2:2016. The plates were packaged in aluminum composite foil immediately after production and the foil was sealed.
[0462] According to VDA 278 (October 2011), the VOC value is defined as the "total amount of volatile to moderately volatile substances". It is calculated in toluene equivalent. The method described in this recommendation allows the determination of VOC values up to n-pentacosane (C 25 ) substances to be measured and analyzed.
[0463] The FOG value is defined as "the total amount of low-volatility substances eluted from the retention time of n-tetradecane (inclusive)". It is calculated on a hexadecane equivalent basis. 14 ” to “C 32 " can be used to measure and analyze substances within the boiling range of .
[0464] Average fiber diameter
[0465] The average fiber diameter is determined according to ISO 1888:2006(E), method B, 1000x microscope magnification.
[0466] B. Preparation of Polymer Compositions
[0467] a) Preparation of single active site catalyst system
[0468] Catalysts used in the examples of the present invention
[0469] Catalyst complex
[0470] The following metallocene complexes have been used as described in WO 2019 / 179959:
[0471]
[0472] Preparation of MAO-silica supports
[0473] A steel reactor equipped with a mechanical stirrer and a filter screen was flushed with nitrogen, and the reactor temperature was set to 20°C. Next, silicon dioxide (5.0 kg) of the grade DM-L-303 of AGC Si-Tech Company pre-calcined at 600°C was added from the feed barrel, followed by careful nitrogen pressurization and decompression using a manual valve. Then, toluene (22 kg) was added. The mixture was stirred for 15 min. Next, a 30 wt % solution (9.0 kg) of MAO from Lanxess in toluene was added through the feed line at the top of the reactor within 70 min. Then, the reaction mixture was heated to 90°C and stirred for another two hours at 90°C. The slurry was allowed to settle and the mother liquor was filtered off. At 90°C, the catalyst was washed twice with toluene (22 kg), followed by settling and filtering. The reactor was cooled to 60°C and the solid was washed with heptane (22.2 kg). Finally, the MAO treated SiO2 was dried at 60°C under a nitrogen stream for 2 hours and then dried under vacuum (-0.5 bar gauge pressure (barg)) with stirring for 5 hours. The MAO treated support was collected as a free flowing white powder, which was found to contain 12.2% Al by weight.
[0474] Preparation of single active site catalyst system (SSCS)
[0475] At 20°C, 30 wt% MAO (0.7 kg) in toluene was added to a nitrogen blanketed steel reactor via a burette. Toluene (5.4 kg) was then added under stirring. The metallocene complex (93 g) as described above was added from a metal cartridge, followed by rinsing with 1 kg toluene. The mixture was stirred for 60 minutes at 20°C. Trityl tetrakis(pentafluorophenyl)borate (91 g) was then added from a metal cartridge, followed by rinsing with 1 kg toluene. The mixture was stirred for 1 h at room temperature. The obtained solution was added to the stirred cake of the MAO-silica support as prepared above within 1 hour. The cake was left for 12 hours, followed by drying for 2 hours at 60°C under a N2 flow, and further drying for 5 hours under vacuum (-0.5 bar gauge) under stirring. The dried catalyst was sampled in the form of a pink free-flowing powder containing 13.9% Al and 0.11% Zr.
[0476] b) Preparation of Ziegler-Natta catalyst system
[0477] Ziegler-Natta catalyst system has been used
[0478] Chemicals used:
[0479] 20% ethylbutylmagnesium (Mg(Bu)(Et), BEM) in toluene, provided by Chemtura
[0480] 2-Ethylhexanol, supplied by Amphochem
[0481] 3-Butoxy-2-propanol-(DOWANOL TM PnB) provided by Dow
[0482] Bis(2-ethylhexyl) citraconic acid ester, provided by SynphaBase
[0483] TiCl4, supplied by Millenium Chemicals
[0484] Toluene, supplied by Aspokem
[0485] 1-254, provided by Evonik
[0486] Heptane, supplied by Chevron
[0487] Preparation of alkoxy magnesium compounds
[0488] The alkoxymagnesium solution was prepared by adding a mixture of 4.7 kg of 2-ethylhexanol and 1.2 kg of butoxypropanol to 11 kg of a 20 wt% toluene solution of ethylbutylmagnesium (Mg(Bu)(Et)) in a 20 L stainless steel reactor under stirring (70 rpm). During the addition, the reactor contents were maintained below 45°C. After the addition was complete, the reaction mixture was mixed (70 rpm) at 60°C for 30 minutes. After cooling to room temperature, 2.3 kg of the donor bis(2-ethylhexyl) citraconic acid ester was added to the alkoxymagnesium solution, maintaining the temperature below 25°C. Mixing was continued for 15 minutes under stirring (70 rpm).
[0489] Preparation of solid catalyst component ZNCS
[0490] 20.3 kg of TiCl4 and 1.1 kg of toluene were added to a 20 L stainless steel reactor. Mixing at 350 rpm and maintaining the temperature at 0°C, 14.5 kg of the prepared alkoxymagnesium compound was added over 1.5 hours. 1.7 L of After 1-254 and 7.5 kg of heptane and mixing at 0° C. for 1 hour, the temperature of the formed emulsion was raised to 90° C. within 1 hour. After 30 minutes, the mixing was stopped, the catalyst droplets solidified, and the catalyst particles formed were allowed to settle. After settling (1 hour), the supernatant was siphoned off. The catalyst particles were then washed with 45 kg of toluene at 90° C. for 20 minutes, followed by two heptane washes (30 kg, 15 min). During the first heptane wash, the temperature was reduced to 50° C., and during the second wash, the temperature was reduced to room temperature. The catalyst thus obtained was used with triethylaluminum (TEAL) as a cocatalyst and dicyclopentyldimethoxysilane (D-donor) as a donor. The ratios used were: TEAL / Ti: 230 mol / mol, TEAL / donor: 40 mol / mol.
[0491] Table 1: Polymerization conditions of polymers 1 and 2 and properties of polymers 1 to 3
[0492]
[0493] Table 2: Polymerization conditions and properties of polymer 4
[0494]
[0495]
[0496] Table 3: Fiber reinforced composite materials and their properties
[0497] CE1 CE2 IE1 Poly1 [weight%] - 49.1 - Poly2 [weight%] - - 49.1 Poly3 [weight%] 49.1 - - Poly4 [weight%] 28.0 28.0 28.0 GF [weight%] 20 20 20 AP [weight%] 1.5 1.5 1.5 AO [weight%] 0.4 0.4 0.4 CB [weight%] 0.5 0.5 0.5 HPP [weight%] 0.5 0.5 0.5 <![CDATA[MFR2]]> [g / 10min] 12.4 16.7 13.3 Screw (1400 bar) [mm] 1174 1117 1223 Tensile modulus [MPa] 4693 4598 4648 Tensile Strength [MPa] 83.8 82.0 83.7 Elongation at break [%] 3.17 3.27 3.18 Simply supported beam <![CDATA[[kJ / m 2 ]]]> 48.6 50.6 50.3 HDT [℃] 159.1 153.5 153.1 VOC [μg / g] 159 45 86 FOG [μg / g] 497 206 355
[0498] "AO" is a mixture of sterically hindered phenol pentaerythritol tetrakis(3-(3',5'-di-tert-butyl-4-hydroxyphenyl)-propionate (CAS-no. 6683-19-8, commercially available as Irganox 1010 from BASF SE, Germany) and phosphorus-based antioxidant tris(2,4-di-tert-butylphenyl) phosphite (CAS-no. 31570-04-4, commercially available as Irgafos 168 from BASF SE, Germany) in a weight ratio of 1:1;
[0499] “GF” is a commercial product ECS 03T-480H of Nippon Electric Glass Co., Ltd. having a filament diameter of 10.5 μm and a strand length of 3 mm;
[0500] "AP" is Scona's adhesion promoter SCONA TPPP 8112GA, which is a polypropylene functionalized with maleic anhydride, having a maleic anhydride content of 1.4 wt% and an MFR of about 80 g / 10 min (190° C., 2.16 kg);
[0501] "CB" is the commercial carbon black masterbatch "Plasblak PPP6331" from Cabot of Germany
[0502] "HPP" is a commercial propylene homopolymer HC001 from Borealis AG having a melt flow rate MFR2 of 2.7 g / 10 min, used as carrier material for the additive.
Claims
1. A fiber-reinforced composite material comprising (a) 30 to 60 wt. % of a polypropylene (PP1), based on the fiber-reinforced composite material, (b) 10 to 40 wt.-%, based on the fiber reinforced composite, of a heterophasic propylene copolymer (HECO), wherein the heterophasic propylene copolymer (HECO) comprises a propylene homopolymer (H-PP2) and an ethylene-propylene rubber (EPR), (c) 10 to 40 wt% of glass fiber (GF), based on the fiber-reinforced composite material, and (d) 0.05 to 5.0 wt. % of a compatibilizer (CA), based on the fiber-reinforced composite material, The total amount of the polypropylene (PP1), the heterophasic propylene copolymer (HECO), the glass fibers (GF) and the compatibilizer (CA) in the fiber reinforced composite material is at least 95 wt.%, Wherein further, the polypropylene (PP1) has (i) a melt flow rate MFR2 (230° C., 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, (ii) not more than 0.5% by weight 13 The comonomer content, if any, determined by C-NMR spectroscopy is ethylene, (iii) a molecular weight distribution (MWD) as determined by gel permeation chromatography (GPC) in the range of greater than 4.5 to less than 8.5, and (iv) Pass in the range of 0.20 to 1.00% 13 2,1 regio defects determined by C-NMR spectroscopy, Wherein still further, the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) has (v) Pass in the range of 0 to less than 0.10% 13 2,1 regiodefects determined by C-NMR spectroscopy.
2. A fiber reinforced composite material according to claim 1, wherein the glass fibers are embedded in a continuous phase comprising at least 98 wt.-% of a mixture of the polypropylene (PP1) and the heterophasic propylene copolymer (HECO).
3. A fiber reinforced composite material according to claim 1 or 2, wherein the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) has a melt flow rate MFR2 (230°C, 2.16 kg) measured according to ISO 1133 in the range of 40.0 to 250 g / 10 min, provided that the melt flow ratio MFR2 between the polypropylene (PP1) and the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) [MFR2(PP1) / MFR2(H-PP2)] is in the range of 0.80 to 1.
20.
4. The fiber reinforced composite material according to any of the preceding claims, wherein the weight ratio between the mixture of the polypropylene (PP1) and the propylene homopolymer (H-PP2) and the ethylene-propylene rubber (EPR) [((PP1) + (H-PP2) / (EPR)] is in the range of 75:25 to 95:
5.
5. A fiber reinforced composite material according to anyone of the preceding claims, wherein the weight ratio between the polypropylene (PP1) and the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) [(PP1) / (H-PP2)] is in the range of 60:40 to 80:
20.
6. A fiber reinforced composite material according to anyone of the preceding claims, wherein the propylene homopolymer (H-PP2) of the heterophasic propylene copolymer (HECO) has a molecular weight distribution (MWD) determined by gel permeation chromatography (GPC) in the range of more than 5.0 to less than 10.
0.
7. The fiber reinforced composite material according to any of the preceding claims, wherein the heterophasic propylene copolymer (HECO) has a melt flow rate MFR2 (230°C, 2.16 kg) measured according to ISO 1133 in the range of 10 to 50 g / 10 min and a 13 Ethylene content determined by C-NMR spectroscopy.
8. The fiber reinforced composite material according to anyone of the preceding claims, wherein the heterophasic propylene copolymer (HECO) has a xylene cold soluble (XCS) content determined according to ISO 16152 at 25 °C in the range of 22 to 45 wt.-%, and the heterophasic propylene copolymer (HECO) has a xylene cold soluble (XCS) fraction in the range of 40 to 60 mol-%. 13 Ethylene content measured by C-NMR.
9. A fiber reinforced composite material according to anyone of the preceding claims, wherein the xylene cold soluble (XCS) fraction of the heterophasic propylene copolymer (HECO) has an intrinsic viscosity (IV) measured according to ISO 1628 / 1 (in decalin at 135 °C) in the range of 2.0 to 5.0 dl / g.
10. The fiber reinforced composite material according to anyone of the preceding claims, wherein the polypropylene (PP1) has a fraction eluting below 100°C by Temperature Rising Elution Fractionation (TREF) in the range of 12 to 20 wt.-%.
11. The fiber reinforced composite material according to anyone of the preceding claims, wherein the polypropylene (PP1) is a propylene homopolymer.
12. The fiber-reinforced composite material according to any one of the preceding claims, wherein the glass fibers (GF) are short glass fibers, optionally having an average fiber length of 2.0 to 10.0 mm before mixing.
13. The fiber reinforced composite material according to any one of the preceding claims, wherein the compatibilizer (CA) is a polar modified polypropylene, preferably maleic anhydride grafted polypropylene.
14. The fiber reinforced composite material according to claim 13, wherein the maleic anhydride grafted polypropylene has a maleic anhydride content of 0.1 to 5.0 wt.-%, and a melt flow rate MFR2 (190°C, 2.16 kg) measured according to ISO 1133 of preferably 70 to 250 g / 10 min.
15. The fiber-reinforced composite material according to any one of the preceding claims, wherein the fiber-reinforced composite material consists of (a) 35 to 55 wt. % of the polypropylene (PP1), based on the fiber-reinforced composite material, (b) 20 to 35 wt.-%, based on the fiber reinforced composite material, of the heterophasic propylene copolymer (HECO), (c) 15 to 30 wt.-%, based on the fiber reinforced composite material, of glass fibers (GF), (d) 0.5 to 5.0 wt% of the compatibilizer (CA), based on the fiber-reinforced composite material, and (e) 0.1 to 5.0 wt% of an additive, based on the fiber-reinforced composite material.
